A study on generating a map for selection of optimum power generation cycles used for Enhanced Geothermal Systems. (15th August 2017) - Zhu, Jialing; Hu, Kaiyong; Zhang, Wei; Lu, Xinli
Abstract: A useful map is generated for selecting optimum power generation cycles used for Enhanced Geothermal Systems. Detailed analysis on the thermodynamic performance has been carried out for four power generation systems: single-flash (SF), double-flash (DF), flash-organic Rankine cycle (FORC), and double-flash-organic Rankine cycle (DFORC). Only subcritical ORC cycles with R245fa as working fluid are analyzed in the study. The map is generated based on comparisons among the four systems with a goal of increasing the net power output by 20% under the condition that the SF is replaced by one of the upgraded systems (DF, FORC, and DFORC). Geofluid's temperature and dryness have strong influences on the performance of each system. FORC has the best thermodynamic performance when the geofluid's temperature is less than 170 °C. DF should be used if the temperature of the geofluid is greater than 170 °C and the steam dryness is less than 0.2. When the steam dryness is greater than 0.2, either DFORC or DF could be an option, but the DFORC is more attractive under a lower geofluid's temperature condition. In terms of engineering economy, DFORC is the most cost-effective system when the geofluid has a relative high temperature and dryness. FORC has a shorter payback period than DF system under the same geofluid's condition. Highlights: A map for selection of an optimum power generation system used for EGS is obtained. Using upgraded systems to replace the SF system can considerably increase net power output. Geofluid's temperature and dryness have strong influences on net power output of each system. Payback period of each power system is analyzed under different geofluid's conditions.